Feeding microparticle protein diet combined with Lactobacillus sp. on existence of intestinal bacteria and growth of broiler chickens - Cholis, M. A.; Suthama, N.; Sukamto, B. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of the study was to evaluate feeding effect of microparticle protein derived from soybean meal and fish meal combined with Lactobacillus sp. at 1.2 mL on physiological condition of digestive tract and productivity of broiler. Total of 192 broiler, with initial body weight was 481.0 ± 67.2 g, given dietary treatment starting on day 21 until day 42. The experiment was assigned in a completely randomized design with 8 treatments and 4 replications. Dietary treatment were 21% intact protein (T0), 18% intact protein (T1), 21% microparticle protein (T2), 18% microparticle protein (T3), T0+Lactobacillus sp.1.2 mL (T4), T1+Lactobacillus sp.1.2 mL (T5), T2+Lactobacillus sp.1.2 mL (T6), T3+Lactobacillus sp.1.2 mL (T7). Parameters measured were total ileal lactic acid bacteria (LAB), Coliform and pH, rate of passage, daily body weight gain (DWG) and also carcass weight. Data were subjected to analysis of variance and followed by Duncan multiple range test (P<0.05). Experimental results showed that microparticle protein diet added with Lactobacillus sp. (P<0.05) increased total LAB and DWG, but decreased Coliform population, and slowed down the rate of passage. However, carcass weight was not significantly affected by treatments. Feeding microparticle protein (18%) with addition of Lactobacillus sp. (1.2 mL) can improve to be better condition of digestive tract based on higher LAB and lower Coliform populations, and increase daily body weight gain with the same carcass weight.